The Borneo Cat / Nur Izzatie Mat Nor - Mat Nor, Nur Izzatie
Sarawak is a state is Malaysia that is located is northwest Borneo Island. The capital state of Sarawak is Kuching and it is a very popular destination among the travellers. Also looms as land of the hornbills, the uniqueness and beautiful culture is Sarawak play as important role is attracts the tourist to visit and learn their ethnicity. Kuching is the largest city on the island of Bowe with a population of 325 132. According to Sarawak tourism, there are so many versions of where the same of Kuching came from. Kuching (cat) takes from Chinese word 'kochis', which swaps harbour or the same of roata kucbisg (cats eye) related to the lychee fruit grows there. Since there is no official mascot representing Kuching, this character design was developed to improve the promotional strategy is a better way.